Insecurity, loneliness and their impacts on Left behind [liushou] women, children and the elderly in Chinese villages -- a Commentary - FENG, HAIYING; Squires, Victor (Advances in Social Sciences Research Journal, 2022)
Change is occurring at a rapid rate in China. Policy reforms, regional development are going ahead at an unprecedented pace. Inevitably, some strata of society have been left behind. This paper focuses on the plight of the ‘left behind’ who comprise mainly children who are in the care of their grandparents, some of whom are elderly. New developments in agriculture (now more highly femininized) innovative land transfer policy, and land consolidation all have an impact on creation of ‘hollow villages’. We assess the importance of current and past developments and conclude with some recommendations about future research priorities and suggestions to local government officials and decision makers.